Genetic variation of blast (Pyricularia oryzae Cavara) resistance in rice (Oryza sativa L.) accessions widely used in Kenya - Fukuta, Yoshimichi (Breed Sci, 2019)
A total of 47 rice accessions collected from Kenya were investigated the genetic variations and classified into two cluster groups, A and B, by polymorphism data of 65 simple sequence repeat (SSR) markers. Clusters A and B corresponded to Japonica and Indica Groups, respectively. The number of Japonica Group accessions was limited in comparison with those of the Indica Group. Based on their patterns of reaction to standard differential blast isolates (SDBIs), these accessions and 57 control cultivars including differential varieties and several accessions harboring partial resistance genes were classified again into three cluster groups: Ia (high resistance), Ib (intermediate resistance) and II (susceptible). The rice accessions from Kenya were classified only into groups Ia and Ib. The accessions from Kenya were finally classified into three categories, A-Ia, B-Ia and B-Ib, based on the two classifications of polymorphism of SSR markers and resistance. The Indica Group accessions had wider genetic variation for blast resistance than did the Japonica Group accessions. The three leading cultivars (Basmati 217, Basmati 370 and ITA 310) categorized into Cluster group Ia were susceptible to some SDBIs from Kenya. The genetic variation for blast resistance in Kenya was demonstrated as the first report using SDBIs.